Document analysis proceedings - Pal Umapada ed.; International Workshop on Document Analysis; International workshop on document analysis Kolkata, India 8-11 Mar 2005 (New Delhi Allied Publishers, 2005)
This International Workshop on Document Analysis discusses the valuable works of the participants. Their lectures cover several important aspects like document understanding, on-line and off-line handwriting recognition, graphics recognition, analysis of historical documents, biometry, postal automation, information retrieval etc.
Keywords: Computer pattern recognition; Document analysis